Antidepressant potential of nitrogen-containing heterocyclic moieties: An updated review - Nadeem Siddiqui; Andalip; Sandhya Bawa; Ruhi Ali; Obaid Afzal; M Jawaid Akhtar; Bishmillah Azad; Rajiv Kumar (Wolters Kluwer Medknow Publications, 2011)
Depression is currently the fourth leading cause of disease or disability worldwide. Antidepressant is approved for the treatment of major depression (including paediatric depression), obsessive-compulsive disorder (in both adult and paediatric populations), bulimia nervosa, panic disorder and premenstrual dysphoric disorder. Antidepressant is a psychiatric medication used to alleviate mood disorders, such as major depression and dysthymia and anxiety disorders such as social anxiety disorder. Many drugs produce an antidepressant effect, but restrictions on their use have caused controversy and off-label prescription a risk, despite claims of superior efficacy. Our current understanding of its pathogenesis is limited and existing treatments are inadequate, providing relief to only a subset of people suffering from depression. Reviews of literature suggest that heterocyclic moieties and their derivatives has proven success in treating depression.